Penerapan Teaching Practic Seni Rupa pada Anak Usia Dini - Octavia, Fadilla Mizratul; Balqis, Aisyah Shinta; Lestari, Juli; Seisky, Seisky; Fauza, Hilyatul; Khaira, Ummi; Deswita, Miranda; Dewi, Ayu Citra (Institut Agama Islam Sumatera Barat, 2024)
This study aims to identify the role of art in early childhood learning, evaluate the effectiveness of the learning approach through play with art with the research theme